KSPPS Financing, Product Innovation, and Technology as Determinants of MSME Growth in Pekalongan City - Nur Fani Arisnawati (AL-FALAH : Journal of Islamic Economics, 2022)
Purpose: This study aims to determine the effect of KSSPS Financing, Product and Technology Innovation as Determinants of Growth of MSMEs in Pekalongan City. This study uses descriptive analysis, with a quantitative approach.Design/Method/Approach : The data collection method used in this study was a closed questionnaire. The data was processed by multiple regression analysis with SPSS tools. Prior to data analysis, the instrument was tested with validity and reliability tests. The analysis prerequisite test was also carried out to fulfill the requirements for the regression model data analysis with normality test, linearity test, multicollinearity test and heteroscedasticity test.Findings: The results of this study indicate that there are only 2 independent variables that have a positive and partially significant effect on the dependent variable, namely the product innovation variable with a value of tcount 3.783 > ttable 1.665 with a significance value of 0.000 <0.05 and technology variable with tcount 4.734 > ttable 1.665. with a significance value of 0.000 <0.05. While the KSPPS financing variable partially has no effect on the growth of MSMEs because tcount -0.000 < ttable 1.665 with a significance value of 0.996 > 0.05. However, simultaneously all independent variables affect the dependent variable with a value of fcount 19.001 > ftable 2.72 and a significance value of 0.000 <0.05.Originality/Values: The main contribution of this research concern on find out the benefits of KSPPS Financing to effectively improve the welfare of MSME’s in Pekalongan City.